НАПРЯМИ ПІДВИЩЕННЯ СОЦІАЛЬНОЇ СТІЙКОСТІ ПЕРСОНАЛУ НА ПІДПРИЄМСТВАХ НАФТОГАЗОВОГО КОМПЛЕКСУ - Зелінська, Г. О. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The article substantiates the directions of increase of social stability of personnel at the domestic oil and gas enterprises. The components that determine its essence are revealed. It is found that effective economic activity of the enterprise in market conditions requires organization of management on a conceptually new basis.